(untitled) (Heritage, 2020)
Sort of (Pa kao) by Vladimir Tabasević is a novel of poetic texture and ambiguous atmosphere, which achieves semantic multilayeredness through its willful incompleteness. Simple in a plot but complex in a narrative sense, burdened with the narrator’s simultaneous disclosure and disguise of his own worldview, Sort of demands reader’s effort to discern in theoretical-philosophical discourse that covers the narrator’s vast psychological ballast. We analyze the novel in light of the psychological vulnerability of the narrator Emil, and the paranoid progression that ends with the psychotic episode in which he becomes the killer. Emil writes his personal history by incorporating everything into a hostile scheme, constantly questioning everyone else’s motives, and repeating his truths obsessively, projecting them into others, which is all indicative of a paranoid personality moving toward a psychotic episode and an experience of depersonalization. The novel puts the reader at the same task the narrator is constantly confronted with: he must discern between what is and what is not told, thus delving into Emil’s early trauma, narcissistic injury and feelings of ontological insecurity, all causes of paranoid psychopathology.